Palestine in crisis - Kirchwey, Freda (Nation Associates)
Palestine and Bevin (In The Nation of June 22, 1946) -- Will the Arabs revolt? (In The Nation of July 13, 1946) -- Obligations in Palestine (In The Nation of July 27, 1946) -- The battle of Palestine (In The Nation of August 3, 1946).